Dietary quality and nutrition in Myanmar: Past progress, current and future challenges - Mahrt, Kristi; Headey, Derek D.; Ecker, Olivier; Comstock, Andrew R.; Tauseef, Salauddin (International Food Policy Research Institute, 2023)
In the decade prior to the COVID-19 pandemic, Myanmar was in the midst of a dietary transition driven by rapid economic growth and urbanization. In this study, we first use national survey data to compare household diets in 2015 to the healthy diet recommendations of food-based dietary guidelines adapted for Myanmar, as well as estimated nutrient consumption relative to recommended intakes. We use these food group and nutrient consumption gaps to estimate a new measure of multidimensional dietary deprivation developed by Pauw et al. (2022), and a novel extension of that index to nutrient deprivation. Both deprivation indices are strongly negatively correlated with total household expenditure. We then use food demand estimation to estimate income and own price elasticities, which reveal strong preferences for animal-sourced foods, but weaker preferences for vegetables and pulses. Expenditure data also point to strong demand for oils/fats – a problem observed throughout developing Asia (Pingali and Abraham 2022) – and for food away from home, which partially explains the rising burden of overweight/obesity in Myanmar. Moreover, since most nutrient-dense foods are income- and price-elastic, estimated income elasticities suggest that recent declines in household income and increases in food prices in Myanmar will result in declining dietary diversity. We show that this is indeed the case utilizing household phone surveys conducted in recent years. We first use a food vendor survey to show that the cost of a healthy diet increased by 61 percent between September 2021 and September 2022. Next, we analyze a rural Dry Zone panel survey implemented 10 times over 2020-2021 and find that maternal and child dietary diversity both declined significantly as Myanmar’s economic situation deteriorated. Then, in a nationally representative phone survey conducted quarterly in 2022 over a period of rapid food inflation, we find further deterioration in diet quality among adults, but no deterioration among children 6-23 months of age, suggesting parents may be trying to insulate their children from the worst effects of the crisis. Finally, we conclude the paper by discussing policy and program options in very difficult political circumstances. Malnutrition is a multidimensional problem requiring multisectoral solutions, but at present the breakdown in the provision of even basic services makes significant progress highly unlikely, and reversing the recent deterioration in dietary quality and nutrition will surely require resolution of Myanmar’s political crisis. In the interim, we discuss three potentially effective types of interventions: (1) rice fortification to reduce micronutrient deficiencies; (2) homestead food production to improve dietary quality in farm households and rural and peri-urban communities; and (3) nutrition-sensitive social protection for vulnerable mothers and young children, with transfers ideally accompanied by nutrition education interventions.